THE ANALYSIS OF STUDENTS’ DIFFICULTIES IN PRONOUNCING ENGLISH AFFRICATIVE CONSONANTS AT THE ENGLISH EDUCATION PROGRAM OF UNIVERSITAS JAMBI - Volya, Duty; A'yuni, Indah Qurrata (Universitas Jambi, 2024)
This research analyzes the difficulties in pronouncing affricative consonants for the English Education department of Universitas Jambi students. This study uses a mixed method, which uses qualitative and quantitative methods to collect the data. The sample of this research was 10 students registered in 2020 at the Universitas Jambi English Education Department. The researcher used a test and an interview as the instruments. This research results from 10 students; 2 of 10 were categorized as high ability, 4 of 10 were categorized as average ability, and 4 of 10 were categorized as low ability. The average score was 54,59, categorized as poor according to the percentage scale by Djumingin .S (2017:596). From the interview results, according to Antaris and Omulu (2019), factors are language origin, age, exposure, inherent phonetic capability, language and ego, and last, effort and commitment to proper pronunciation. The students found it difficult to pronounce English because English is not their first language or mother language. The student always uses their mother language rather than English in daily communication. Therefore, the results of this study with the low average score of the students were caused by English not being their first language and the rare use of English in daily conversations.